Organic Carbons and Fatty Acids in Antarctic Saline Lakes - Genki MATSUMOTO; Takahisa HANYA (National Institute of Polar Research, 1977)
Total organic carbon (TOC), extractable organic carbon (EOC), and fatty acids were determined in bottom waters of Lakes, Vanda, Bonney, and Fryxell in the Dry Valleys of Victoria Land, Antarctica. The high concentrations of TOC and EOC were found, ranging from 18.6 to 63.8 mg/l and from 3.8 to 9.1 mg/l respectively. Fatty acids ranging from C_ (carbon numbers: numbers of unsaturation) to C_ including C_ and C_ were determined by using a combined gas chromatograph-mass spectrometer (GC-MS), and their total concentrations were 2.8-19μg/l. Furthermore, phenylacetic acid was identified in the bottom waters of Lake Bonney. The sources of those organic compounds may be due to the lake organisms, such as algae, bacteria, and fungi.